Kujang Salakageni Association Preserves Debus Tradition Amidst Modern Turmoil in Bogor - WIDIYA, Sri (PT Batara Swastika Harati, 2024)
This research explores the efforts of Paguyuban Kujang Salakageni in Bogor Regency, Indonesia, to preserve the traditional art of Debus amidst the challenges posed by modernity. As globalization and modernization threaten the resilience of local cultures, the Salakageni community, made up primarily of young individuals, remains committed to safeguarding and promoting this unique cultural heritage. This study uses a qualitative approach and includes data collection methods like observations, interviews, and documentation studies. The findings reveal that preserving the Debus tradition is a significant challenge. In contemporary society, Debus performances are often viewed by certain segments of the population as mere forms of entertainment. The younger generation, in particular, tends to perceive the tradition as outdated, which makes it less attractive compared to modern forms of music and dance. However, despite these challenges, Salakageni continues to perform at various community events, not only within Bogor but also in neighboring regions. In spite of struggling for support from both the private sector and government institutions, the group remains dedicated to organizing Debus performances in public spaces, funded out of their own pockets. Their efforts are driven by a deep passion and a sense of moral responsibility to preserve and pass on this traditional art form, ensuring the continuity of the nation’s cultural heritage for future generations.